Effect of pore structure on the removal of clofibric acid by magnetic anion exchange resin. (January 2018) - Tan, Liang; Shuang, Chendong; Wang, Yunshu; Wang, Jun; Su, Yihong; Li, Aimin
Abstract: The effect of pore structure of resin on clofibric acid (CA) adsorption behavior was investigated by using magnetic anion exchange resins (ND-1, ND-2, ND-3) with increasing pore diameter by 11.68, 15.37, 24.94 nm. Resin with larger pores showed faster adsorption rates and a higher adsorption capacity because the more opened tunnels provided by larger pores benefit the CA diffusion into the resin matrix. The ion exchange by the electrostatic interactions between Cl-type resin and CA resulted in chloride releasing to the solution, and the ratio of released chloride to CA adsorption amount decreased from 0.90 to 0.65 for ND-1, ND-2 and ND-3, indicating that non-electrostatic interactions obtain a larger proportional part of the adsorption into the pores. Co-existing inorganic anions and organic acids reduced the CA adsorption amounts by the competition effect of electrostatic interaction, whereas resins with more opened pore structures weakened the negative influence on CA adsorption because of the existence of non-electrostatic interactions. 85.2% and 65.1% adsorption amounts decrease are calculated for resin ND-1 and ND-3 by the negative influence of 1 mmol L −1 NaCl. This weaken effect of organic acid is generally depends on its hydrophobicity (Log Kow) for carboxylic acid and its ionization degree (pKb) for sulfonic acid. The resins could be reused with the slightly decreases by 1.9%, 3.2% and 5.4% after 7 cycles of regeneration, respectively for ND-1, ND-2 and ND-3, suggesting the ion exchange resin with larger pores are against its reuse by the brine solution regeneration. Graphical abstract: Image 1 Highlights: Electrostatic interaction (EI) mainly contributes to the CA adsorption. Non-EIs obtain a larger proportional part of adsorption into the pores. The competition effect by anions is weakened for resin with more opening pores. The reusability of resin decrease with pores more opening caused by the non-EIs.